The Inheritance and Development of the Gold Ornament Culture of the Women of Xunpu - Wang, Mengqi (International Journal of Humanities and Social Science, 2026)
The gold ornaments of the Xunpu Women are the core material carrier of marine folk customs in southern Fujian. They form a "symbolic symbiosis" with the hairpin custom and are an important part of the national intangible cultural heritage. Quanzhou has attracted global attention after its successful application as a World Heritage Site. Its development is deeply tied to the Maritime Silk Road trade. It has evolved through the Han, Song, Yuan, Ming and Qing dynasties, integrating Islamic culture and traditional Chinese auspicious meanings, forming a unique style with maritime culture as the core. Gold ornaments, with gold hairpins, gold earrings and gold combs as the core types, have the characteristics of symbolization, life-oriented and cultural integration. They are the memory carrier, cultural identity mark and emotional sustenance of the Maritime Silk Road. However, contemporary inheritance faces difficulties such as shallow cultural connotation, faulty skill inheritance, and fragmented protection systems. In order to achieve living inheritance, it is necessary to explore its deep value through in-depth dissemination of cultural tourism, dual-track talent cultivation in schools and apprentices, integration of tradition and modern innovation, and comprehensive policy guarantees covering skills and customs, so that the memory and folk wisdom of the Maritime Silk Road carried by this intangible cultural heritage can continue to pass on vitality in the new era.